2015
DOI: 10.1007/s00213-015-3938-6
|View full text |Cite
|
Sign up to set email alerts
|

Application of cross-species PET imaging to assess neurotransmitter release in brain

Abstract: RationaleThis review attempts to summarize the current status in relation to the use of positron emission tomography (PET) imaging in the assessment of synaptic concentrations of endogenous mediators in the living brain.ObjectivesAlthough PET radioligands are now available for more than 40 CNS targets, at the initiation of the Innovative Medicines Initiative (IMI) “Novel Methods leading to New Medications in Depression and Schizophrenia” (NEWMEDS) in 2009, PET radioligands sensitive to an endogenous neurotrans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
73
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 266 publications
(325 reference statements)
0
73
0
1
Order By: Relevance
“…These studies showed reduced cortical radioligand binding, albeit to a lesser extent than striatal [ 11 C]raclopride displacement, that indicated that these radiotracers may allow for monitoring of changes in cortical synaptic dopamine concentrations when endogenous dopamine was available for release, also in clinical experiments 4 . The changes in radiotracer binding were proportional to changes in dopamine concentrations as measured in microdialysis experiments; findings that reflect modulation of dopamine release into the synaptic gap instead of inherently reflecting changes in the extracellular fluid dopamine concentration across drugs with different modes of action 2 .…”
Section: Pet Radiotracers That Have Enabled Imaging Of Neurotransmmentioning
confidence: 89%
See 4 more Smart Citations
“…These studies showed reduced cortical radioligand binding, albeit to a lesser extent than striatal [ 11 C]raclopride displacement, that indicated that these radiotracers may allow for monitoring of changes in cortical synaptic dopamine concentrations when endogenous dopamine was available for release, also in clinical experiments 4 . The changes in radiotracer binding were proportional to changes in dopamine concentrations as measured in microdialysis experiments; findings that reflect modulation of dopamine release into the synaptic gap instead of inherently reflecting changes in the extracellular fluid dopamine concentration across drugs with different modes of action 2 .…”
Section: Pet Radiotracers That Have Enabled Imaging Of Neurotransmmentioning
confidence: 89%
“…To date, the main class of radiotracers shown to be sensitive for endogenous neurotransmitter release is specific to the dopamine receptor system (for an overview see for example Finnema et al 2015 2 ). Current research indicates that novel radiotracers developed for the serotonin (5-hydroxytryptamine, 5-HT), the opioid and the cholinergic system are also sensitive for changes in extracellular concentrations of their respective neurotransmitters.…”
Section: Pet Radiotracers That Have Enabled Imaging Of Neurotransmmentioning
confidence: 99%
See 3 more Smart Citations